The Mertiyo Rathors of Merto, Rajasthan : Select Translations Bearing on the History of a Rajput Family, 1462-1660, Volumes 1-2 - Ziegler, Norman Paul, 1943-; Saran, Richard Davis (Michigan papers on South and Southeast Asia, 2020)
This book is a treasure for scholars of Rajput history. Richard D. Saran and Norman P. Ziegler, whose contributions to Rajput studies are well known to specialists in the field, have given us a work of deep and exacting scholarship. It is the culmination of decades devoted to the study of Middle Marwari chronicles from Rajasthan. The sources translated here provide access to the fortunes of a branch of the Jodhpur royal family, and in doing so they illuminate the larger world of Rajputs in the middle period. The translations are accompanied by an extensive explanatory apparatus taking various forms, which includes a valuable essay on Rajput social organization, complete genealogies, and biographies of all the major personages of the chronicles.